2010 Joint Rail Conference, Volume 2 2010
DOI: 10.1115/jrc2010-36020
|View full text |Cite
|
Sign up to set email alerts
|

Update on Alternative Occupant Volume Testing

Abstract: This paper describes the conduct of the first of a series of quasi-static compression tests of rail passenger equipment being done to examine occupant volume strength. Specifically, this program is investigating methods of evaluating occupant volume integrity when loads are placed along the collision load path of the occupant volume. Budd Pioneer car 244 has been chosen as the test article to examine alternative occupant volume loading strategies. Since this car has been involved in several impact tests as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Previously, an 800,000 pound compression test of Budd Pioneer #244 was performed on January 20, 2010 [8]. While preliminary results of this test were reported, detailed review of the test results indicated some anomalies.…”
Section: Test Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, an 800,000 pound compression test of Budd Pioneer #244 was performed on January 20, 2010 [8]. While preliminary results of this test were reported, detailed review of the test results indicated some anomalies.…”
Section: Test Setupmentioning
confidence: 99%
“…3 crash tested. Pioneer #244 had been used in five dynamic impact tests [8]. Successful completion of the 800,000 pound compressive test would verify the suitability of this car for further testing.…”
Section: Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this previous program demonstrated that the 1.2 million pound crippling load adopted by the ETF as one of its OVI criteria was a reasonable description of the minimum crippling load to be found in an 800-kip compliant railcar of conventional design. The progress of and results from the previous research program have been detailed in several recent publications [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%